Estimation of Chlorophyll-A Concentration in Aquatic Ecosystems Northwest Arabian Gulf Using Remote Sensing - Al-Fartusi, Adel J; Malik , Mutasim I.; Abduljabbar , Hameed M. (Mesopotamian Journal of Marine Sciences, 2025)
One of the essential components of life is water, and that is why its monitoring is fundamental. The purpose of this research, therefore, was to estimate the concentration of chlorophyll-a using remote sensing data. Chlorophyll-a concentration in water is an indicator of phytoplankton density and, consequently, water quality, which in turn is crucial, as it represents the base of the ecological life in seas and oceans. Any increase or decrease in the number of phytoplankton may contribute to the disruption of the ecological cycle in the seawater. The study area was located in the northwest Arabian Gulf. The concentration of chlorophyll-a was mapped based on images captured by the Medium Resolution Imaging Spectroradiometer on Aqua Satellite (MODIS) and Operational Land Imager (OLI) sensor. The images were acquired in 2022. Chlorophyll-a concentration was estimated using an algorithm based on Band 4 and Band 5 of Landsat 8,9 OLI. The concentration of chlorophyll-a was found throughout the seasons of the year 2022, and it was found that its highest value is in the winter season and its lowest value is in the spring.